Pengaruh Brand Image, Efektivitas Signal, Dan Persepsi Word Of Mouth Terhadap Keputusan Pembelian Kartu Perdana Telkomsel Di Mojokerto - Ro’isa Zumaroh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of brand image on purchasing decisions for Telkomsel starter packs in Mojokerto. To find out the effect of Signal effectiveness on the purchasing decision of Telkomsel starter packs in Mojokerto. To find out the influence of Word OF Mouth perceptions on buying decisions for Telkomsel starter packs in Mojokerto. research using quantitative methods. The number of samples is 91 respondents (slovin formula). The results of the T (Partial) test in this study showed a significant Brand Image value of 0.003 ≤ 0.05 tcount 3.091, tcount ≥ ttable (3.091 > 1.988) partially significant. Significant value of Signal Effectiveness is 0.569 ≥ 0.05, tcount is 0.572, tcount ≤ ttable (0.572 <1.988) has no effect partially. Perception of Word OF Mouth significant value of 0.002 ≤ 0.05, tcount 3.123, so tcount ≥ ttable (3.123 > 1.988) has a partial effect. The F test obtains a significant value of 0.000, meaning a significant value ≤ 0.05. And the Fcount value obtained is 43.006, the Fcount value ≥ from Ftable (43.006 > 2.71). Brand Image, Signal Effectiveness and Word OF Mouth Perception simultaneously influence purchasing decisions.